(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Digital transformation is penetrating financial sector. Financial sector is challenged by new start-up companies who combine finance and technology, thereby creating disruptive innovations. The authors perform a study on information technology impact on competency management in the financial sector of Latvia based on the technology management competency model.The authors have executed extensive academic literature review and interviews with leading fintech industry experts. The research team performed mixed research combining qualitative and qualitative methods. The process of the quantitative research was designed as a collection of publicly available financial statement data from lursoft.lv (enterprise database) for selected fintech companies and the analysis of financial data by comparing different fintech companies. The process of the qualitative research was designed as face-to-face expert interviews and the definition of central interview questions for the research based on the literature review and related sub-questions. The authors use the one-way analysis of variance technique and prove that competency management differs among fintech companies by comparing average turnover per employee of platform and credit companies. The finding persuades the authors to propose a fundamental fintech competency model to ensure competitiveness and sustainability of fintech companies.The objective of the research is to define a fundamental set of competencies linked with information technology management for financial sector companies to maintain competitiveness. Results prove that current set of competencies employed by fintech companies represents sufficient technical competencies. The conclusions demonstrate that fintech companies tend to have different competency management models. The research team concludes that soft skills development, data analytics using advanced data analytic tools, technology awareness, the ability and experience to use open source technology tools to develop technology solutions without deep technology competency, the ability to see the big picture, and interconnections between processes are competencies of the future.